2020
DOI: 10.1177/0706743720940562
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of COVID-19 on Youth Mental Health, Substance Use, and Well-being: A Rapid Survey of Clinical and Community Samples: Répercussions de la COVID-19 sur la santé mentale, l’utilisation de substances et le bien-être des adolescents : un sondage rapide d’échantillons cliniques et communautaires

Abstract: Objectives: The current novel coronavirus disease of 2019 (COVID-19) pandemic presents a time-sensitive opportunity to rapidly enhance our knowledge about the impacts of public health crises on youth mental health, substance use, and well-being. This study examines youth mental health and substance use during the pandemic period. Methods: A cross-sectional survey was conducted with 622 youth participants across existing clinical and community cohorts. Using the National Institute of Mental Health-developed CRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
147
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 201 publications
(169 citation statements)
references
References 24 publications
11
147
0
Order By: Relevance
“…The first research to emerge was from China. Researchers found adolescents (ages [7][8][9][10][11][12][13][14][15][16][17][18] in the areas with the highest rate of COVID-19 cases and subsequent public health measures to have higher rates of anxiety and depressive symptoms (7). Specifically, the authors found that 22% of their sample was above the clinical cut-off for depression.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The first research to emerge was from China. Researchers found adolescents (ages [7][8][9][10][11][12][13][14][15][16][17][18] in the areas with the highest rate of COVID-19 cases and subsequent public health measures to have higher rates of anxiety and depressive symptoms (7). Specifically, the authors found that 22% of their sample was above the clinical cut-off for depression.…”
mentioning
confidence: 99%
“…Increased rates of mental health problems in adolescents were also reported by parents in Italy and Spain (9). In a Canadian study conducted in April 2020 found that in a community sample of young adults ages 18-28, 13% met criteria for depression and 10% for anxiety (10). The extent to which stress is related specifically to COVID-19 is less clear.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A repeated cross-sectional study comparing clinical and community cohorts of young people aged 14 to 28 years found that clinical cohorts had slightly higher mental health symptoms but community cohorts experienced greater deterioration during the pandemic. 6 Similarly, a Dutch study of over 4,000 cancer survivors and matched normative participants found slightly higher levels of depression and loneliness in the general population. 7 These studies suggest that levels of distress may be similar, or even higher, in healthy populations.…”
mentioning
confidence: 93%